State Functions in The New Realities of The Digital Society (Texas Journal of Multidisciplinary Studies, 2025)
At the present stage, the informational function of the state possesses the key characteristics of the main functions of the state and extends across all branches of government. This article addresses the significance of the informational function of the state as an established area of governmental activity in the context of ongoing digitalization processes. The paper proposes considering the informational function as an independent domain of state activity that requires comprehensive legal regulation